2007
DOI: 10.1002/glia.20601
|View full text |Cite
|
Sign up to set email alerts
|

Gliatrophic and gliatropic roles of PVF/PVR signaling during axon guidance

Abstract: Evidence of molecular and functional homology between vertebrate and Drosophila glia is limited, restricting the power of Drosophila as a model system to unravel the molecular basis of glial function. Like in vertebrates, in the Drosophila central nervous system glial cells are produced in excess and surplus glia are eliminated by apoptosis adjusting final glial number to axons. The underlying molecular mechanisms are largely unknown, as the only gliatrophic pathway known to date in flies is the EGFR and its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…This may reflect conditions in intact insect nervous systems, where survival of glial cells has been demonstrated to depend on trophic factors from nearby neurons and the lack of these factors initiated apoptosis (Jacobs, 2000;Hidalgo et al, 2001;Bergmann et al, 2002;Sen et al, 2004;Learte et al, 2008). In addition, some studies indicated that neurons also depend on glial signals that determine differentiation (Jones et al, 1995), growth (Keen et al, 1994) and survival (Buchanan and Benzer, 1993;Jones et al, 1995;Booth et al, 2000;Shepherd, 2000).…”
Section: Microscopy Research and Techniquementioning
confidence: 92%
“…This may reflect conditions in intact insect nervous systems, where survival of glial cells has been demonstrated to depend on trophic factors from nearby neurons and the lack of these factors initiated apoptosis (Jacobs, 2000;Hidalgo et al, 2001;Bergmann et al, 2002;Sen et al, 2004;Learte et al, 2008). In addition, some studies indicated that neurons also depend on glial signals that determine differentiation (Jones et al, 1995), growth (Keen et al, 1994) and survival (Buchanan and Benzer, 1993;Jones et al, 1995;Booth et al, 2000;Shepherd, 2000).…”
Section: Microscopy Research and Techniquementioning
confidence: 92%
“…Conversely, perturbing VNC development blocks haemocyte migration along the midline and prevents haemocytes from reaching mid-trunk neuromeres and other potential sites of function; hence, haemocyte migration and VNC development are interdependent processes. This interdependence is particularly fascinating given that the key growth factors in haemocyte migration (Pvf2 and Pvf3) also regulate glial cell migrations within the VNC (Learte et al, 2008). Reiterative use of growth factors, such as the Pvfs, reduces the number of genes required to regulate the multitude of processes crucial for development.…”
Section: Interdependence Of Vnc Development and Haemocyte Migrationmentioning
confidence: 99%
“…During embryonic development, programmed cell death (PCD) shapes the embryo, enabling proper development of tissues and organs (Domingos and Steller, 2007;Henson and Hume, 2006;Hipfner and Cohen, 2004;Learte et al, 2008). Specifically, PCD in the developing nervous system has been demonstrated in Drosophila as well as in higher organisms (Brachmann and Cagan, 2003;Buss et al, 2006;Rogulja-Ortmann et al, 2007).…”
Section: Introductionmentioning
confidence: 99%